Ilham D'cipta Sdn. Bhd. / Zulamale Mohd and Fazinushani Mohamed - Mohd, Zulamale; Mohamed, Fazinushani (2001)
This partnership named Ilham D'cipta Sdn Bhd provides curtain booking , carpet, bed sheet, pillowcase, cushion case and wallpaper. They located in Sungai Petani,Kedah. Started their first business in1 January 2002